Assembly of encapsulated water in hybrid bisamides: helical and zigzag water chains1. Issue 7 (21st February 2015) - Bera, Santu; Maity, Sibaprasad; Haldar, Debasish
<x xml:space="preserve">Abstract</x> The addition of water promotes the self-assembly of hybrid bisamides by bridging between the molecules and stabilizes the helical or zigzag one-dimensional water chains.